Behavioral Insights into Digital Payment Innovations - K. R., Sukritha; V, Vimala (Universitas Prasetiya Mulya, 2025)
The growth of digital payments in India has been tremendous, driven by advancements in technology and supportive policy measures. This investigation explores the usage of digital payment systems through the lens of the Technology Acceptance Model (TAM), emphasising Perceived Usefulness (PU) and Perceived Ease of Use (PEU) as key predictors of Behavioural Intention (BI). A survey of 550 respondents reveals that both PU and PEU significantly influence BI, underscoring the significance of perceived utility and simplicity in driving adoption. Furthermore, BI strongly correlates with the Actual Usage of digital payment systems, validating its applicability to real-world behaviour. The study finds no discernible difference in satisfaction levels between male and female consumers. Younger and middle-aged individuals report higher satisfaction than older users, with age as a critical influence. Users’ most significant concern is a perceived lack of security. These findings provide insights to improve digital payment acceptance.